2015
DOI: 10.1037/xge0000035
|View full text |Cite
|
Sign up to set email alerts
|

The conjunction fallacy, confirmation, and quantum theory: Comment on Tentori, Crupi, and Russo (2013).

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Copyright and reuse: City Research Online aims to make research outputs of City, University of London available to a wider audience. Copyright and Moral Rights remain with the author(s) and/or copyright holders. URLs from City Research Online may be freely distributed and linked to. City Research Online: http://openaccess.city.ac.uk/ publications@city.ac.uk Permanent repository link: City Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
2
26
0
3
Order By: Relevance
“…Overall, our result is in line with previous suggestions that degenerate models should be preferred to non-degenerate models, as the latter should be considered as "toy models" only (e.g. Busemeyer and Bruza 2012;Busemeyer et al 2015). The second research hypothesis extends the first one by considering also degenerate models, that is, models in which an answer is represented by a N -D subspace, e.g.…”
Section: Interpretation Of the Results And Relation With General Resesupporting
confidence: 78%
See 1 more Smart Citation
“…Overall, our result is in line with previous suggestions that degenerate models should be preferred to non-degenerate models, as the latter should be considered as "toy models" only (e.g. Busemeyer and Bruza 2012;Busemeyer et al 2015). The second research hypothesis extends the first one by considering also degenerate models, that is, models in which an answer is represented by a N -D subspace, e.g.…”
Section: Interpretation Of the Results And Relation With General Resesupporting
confidence: 78%
“…Consequently, the corresponding probabilities of answering "yes" to questions Q B and Q F depend on the order of presentation of the questions: it is an order effect More importantly, it can be shown that only models that display an order effect are able to account for the conjunction fallacy (cf. Busemeyer et al 2011Busemeyer et al , 2015Busemeyer and Bruza 2012;Bruza et al 2015, p. 388). In other words, the quantumlike models of Sect.…”
Section: Order Effectmentioning
confidence: 99%
“…Les résultats expérimentaux que nous avons obtenus, s'ils ne permettent pas d'exclure les modèles quantiques de façon générale, montrent nettement que leséquations GR ne sont pas vérifiées, et donc que ces modèles quantiques non-dégénérés ne sont pas adéquats d'un point de vue empirique, et ne peuvent pré-tendre rendre compte de l'erreur de conjonction pour les 4 histoires considérées. Ceci confirme certaines intuitions de la littérature (e. g. Busemeyer et al 2015) selon lesquelles les modèles non-dégénérés doivent surtout avoir un rôle illustratif. Nous avons considéré ici des histoires variées, appartenant aux deux types d'erreur de conjonction distingués (AB et MA), ce qui suggère fortement que les erreurs de conjonction en général ne sont pas explicables par des modèles quantiques non-dégénérés.…”
Section: Discussionunclassified
“…Pourêtre légitime, une explication doit reposer sur des modèles empiriquement adéquats. Aussi, nous poursuivrons ici l'étude de l'adéquation empirique de ces modèles quantiques, dans la lignée de travaux ré-cents (e. g. , Pothos et Busemeyer 2013, Busemeyer et al 2015, Boyer-Kassem et al 2016. L'originalité de notreétude consistè a avoir conçu et realisé un protocole experimental qui permet d'observer l'erreur de conjonction comme un effet résultant d'un autre biais cognitif (l'effet d'ordre).…”
Section: Introductionunclassified
See 1 more Smart Citation